Combination of Corn, Cassava and Yellow Sweet Potato as Media Growth of Candida Albicans - Muhammad Taufiq Qurrahman; Fitria Diniah Janah Sayekti; Dwi Haryatmi (GLOBAL HEALTH SCIENCE GROUP, 2022)
Fungal infections are quite common in people in tropical countries including Indonesia. Candida albicans is a fungus that can cause infection in humans. Infection caused by Candida albicans is called candidiasis. Diagnosis of Candida albicans with a culture system aims to identify and confirm the results of microscopic examination. Alternative media for fungal growth from various carbohydrate sources have been widely used. Alternative media for fungal growth used included corn, cassava and sweet potato. This study aims to determine the growth of Candida albicans on media with a combination of corn, cassava and sweet potato. The source of data was obtained from primary data, namely data on the results of differences in growth observed from the number of Candida albicans colonies formed on a combination of corn, cassava, and yellow sweet potato media. Data analysis was carried out by statistical tests, including normality test and homogeneity test. If the normality test and homogeneity test meet the requirements, then proceed with the ANOVA and post hoc tests. The results showed that the growth of Candida albicans after 48 hours of incubation, the average number of colonies on corn-cassava media was 58.4x1011 CFU/ml colonies with a colony diameter of 1 mm. Colonies on yellow sweet potato-corn media were 51.5x1011 CFU/ml with a diameter of 1 mm. Colonies on PDA media were 24.8x1011 CFU/ml with a diameter of 1-2mm. In this study, it can be seen that there is a significant difference (p<0.05) in the growth of Candida albicans fungal colonies in each group of media with the highest colony growth, namely on corn and cassava media.